2020
DOI: 10.3892/ol.2020.11803
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA profiles of HTLV‑1 asymptomatic carriers with monoclonal and polyclonal rearrangement of the T‑cell antigen receptor γ‑chain using massively parallel sequencing: A pilot study

Abstract: In the present pilot study, massively parallel sequencing (MPS) technology was used to investigate cellular small RNA (sRNA) levels in the peripheral blood mononuclear cells (PBMCs) of human T-lymphotropic virus type I (HTLV-I) infected asymptomatic carriers with monoclonal (ASM) and polyclonal (ASP) T cell receptor (TCR) γ gene. Blood samples from 15 HTLV-I asymptomatic carriers (seven ASM and eight ASP) were tested for the clonal TCR-γ gene and submitted for sRNA library construction together with blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 90 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…Moreover, 12 of the 15 bta-miRNAs with relatively weaker negative correlations to AS1 mRNA expression (-0.7 < r < -0.6) also function as tumor suppressors, oncogenes, or both. Our study shows that both miR-532-5p and miR-106b-5p are down-regulated and have a negative correlation with AS1 mRNA expression, which is consistent with the results of another study that showed that miR-532-5p and miR-106a-5p are significantly down-regulated in HTLV-1 asymptomatic carriers [125]. MiR-106b targets the cell cycle regulatory gene p21 (CDKN1A) and is also specifically downregulated in HIV-1 infected CD4 + T cells [126].…”
Section: Plos Onesupporting
confidence: 92%
“…Moreover, 12 of the 15 bta-miRNAs with relatively weaker negative correlations to AS1 mRNA expression (-0.7 < r < -0.6) also function as tumor suppressors, oncogenes, or both. Our study shows that both miR-532-5p and miR-106b-5p are down-regulated and have a negative correlation with AS1 mRNA expression, which is consistent with the results of another study that showed that miR-532-5p and miR-106a-5p are significantly down-regulated in HTLV-1 asymptomatic carriers [125]. MiR-106b targets the cell cycle regulatory gene p21 (CDKN1A) and is also specifically downregulated in HIV-1 infected CD4 + T cells [126].…”
Section: Plos Onesupporting
confidence: 92%
“…These findings underline the role of other not yet recognized molecular pathways related to the role of this miRNA (152). Recently, an sRNA-seq analysis revealed a distinct profile of miRNA expression in the PBMCs of HTLV−1 asymptomatic carriers compared to controls, a fact that may underline their role in latency and malignant hallmark development (153).…”
Section: Viral and Human Microrna Regulation In Human Malignancy Developmentmentioning
confidence: 81%
“…These miRNAs include mmu-miR-98 that were upregulated, and mmu-miR-532 and mmu-miR-744 were downregulated in the same OVA-immunized derived offspring group and others 45 microRNAs that were differentially expressed between evaluated groups. A study suggests mmu-miR-744 as a potent type I interferon inducer [ 51 ] and mmu-miR-523 as a pro-inflammatory cytokine attenuation microRNA [ 52 ]. These observations may indicate that mmu-miR-744 and mmu-miR-523 could eventually influence the balance between IL-17/IFN-γ production, or the pro-inflammatory profile of γδT cells but, to elucidate the role of these and others microRNAs, further experiments need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%